Just subtract 9.
The nth term in this sequence is 4n + 3.
The nth term is: 5-6n
The nth term is 4n-1 and so the next term will be 19
The nth term of a sequence is the general formula for a sequence. The nth term of this particular sequence would be n+3. This is because each step in the sequence is plus 3 higher than the previous step.
nth term is n squared plus three
It is: 2n+9
Double it minus the previous number.
The nth term for that arithmetic progression is 4n-1. Therefore the next term (the fifth) in the sequence would be (4x5)-1 = 19.
As given, the sequence is too short to establish the generating rule. If the second term was 19 and NOT 29, then the nth term is tn = 6*n + 7 or 6(n+1)+1
t(n) = 28 - 9n
It is: nth term = 7n-9
If you mean: 15 11 7 3 then the nth term is 19-4n
The nth term of an arithmetic sequence is given by. an = a + (n – 1)d. The number d is called the common difference because any two consecutive terms of an. arithmetic sequence differ by d, and it is found by subtracting any pair of terms an and. an+1.
The nth term is: 2n+7 and so the next number will be 19
It is: nth term = 5-4n and so the next term will be -19
The nth term is 6n+1 and so the next term will be 31
5 to 7 is 27 to 17 is 1017 to 19 is 219 to 29 is 1029 to 31 is 2there fore following the pattern the nth term is 4131 to 41 is 10
The nth term is 3n+7 and so the next number will be 22
The next term is: 15+4 = 19 The nth term is: 4n-5
The sequence is simply achieved by adding 2 to each value9+2=1111+2=1313+2=1515+2=1717+2=1919+2=21so the nth term can be calculatedThe value of the nth term = the value of (nth-1 term) +2.
you have answered your own question 19 - 3n
If you mean -1 3 7 11 15 then the nth term is 4n-5 and so the next term will be 19